Implementation of Semarang City Regulation Number 5 Year 2014 Regarding the Handling of Street Chlidren, Homeless, and Beggars in Semarang City - Joshua Fernando; Hartuti Purnaweni (Journal of Public Policy and Management Review, 2019)
This study aims to analyze the factors that influence the implementation of Regional Regulation No. 5 of the City of Semarang concerning the handling of street children, vagabonds, and beggars. Qualitative descriptive research. The research locus in the Semarang City Social Service and the Social Services Outreach Team, the Indonesian Gold Foundation, and administrators of the Children's Shelter (RSA) Among Jiwo. Research subjects: street children, TPD team members, and boarders. The data collection technique uses purposive sampling. Sources of data in this study are Primary Data and Secondary Data, with data collection techniques: Observation, Interview, Documentation, Library Study. Data analysis and interpretation techniques used in data processing are data reduction, presentation and conclusion / verification. Research results show that the supporting factors for this implementation are communication and implementing attitudes, while the inhibiting factors are the factors of factors and factors of social and economic conditions of the community. Suggestions can be given is to increase the wages of members of the Semarang City Social Service Outreach Team and improve the quality, quantity of human resources facilities and facilities